Heme Interferes With Complement Factor I-Dependent Regulation by Enhancing Alternative Pathway Activation - Gerogianni, Alexandra; Dimitrov, Jordan D.; Zarantonello, Alessandra; Poillerat, Victoria; Chonat, Satheesh; Sandholm, Kerstin; McAdam, Karin E.; Ekdahl, Kristina N.; Mollnes, Tom E.; Mohlin, Camilla; Roumenina, Lubka T.; Nilsson, Per H. (Frontiers in Immunology, 2022)
Hemolysis, as a result of disease or exposure to biomaterials, is characterized by excess amounts of cell-free heme intravascularly and consumption of the protective heme-scavenger proteins in plasma. The liberation of heme has been linked to the activation of inflammatory systems, including the complement system, through alternative pathway activation. Here, we investigated the impact of heme on the regulatory function of the complement system. Heme dose-dependently inhibited factor I-mediated degradation of soluble and surface-bound C3b, when incubated in plasma or buffer with complement regulatory proteins. Inhibition occurred with factor H and soluble complement receptor 1 as co-factors, and the mechanism was linked to the direct heme-interaction with factor I. The heme-scavenger protein hemopexin was the main contaminant in purified factor I preparations. This led us to identify that hemopexin formed a complex with factor I in normal human plasma. These complexes were significantly reduced during acute vasoocclusive pain crisis in patients with sickle cell disease, but the complexes were normalized at their baseline outpatient clinic visit. Hemopexin exposed a protective function of factor I activity in vitro, but only when it was present before the addition of heme. In conclusion, we present a mechanistic explanation of how heme promotes uncontrolled complement alternative pathway amplification by interfering with the regulatory capacity of factor I. Reduced levels of hemopexin and hemopexin-factor I complexes during an acute hemolytic crisis is a risk factor for heme-mediated factor I inhibition.